Revenge Through Haunting: Expression of Women’s Anger in the Movies, Tookaidoo Yotsuya Kaidan and Sundel Bolong - Rouli Esther Pasaribu; Meilia Widya Ananda (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
Tookaidoo Yotsuya Kaidan (1959) and Sundel Bolong (1981) are horror movies from Japan and Indonesia, respectively, about women who are oppressed by men and subsequently take revenge on them after their deaths. The key similarity between these two movies is that they have central female characters who turn into ghosts in order to express their anger towards their male oppressors. This study aimed to see how women's anger is depicted in Tookaidoo Yotsuya Kaidan and Sundel Bolong, using verbal and visual text analysis and the concept of power by Heilbrun, male gaze by Mulvey, and monstrous-feminine by Creed to read the meaning behind woman’s anger as it is expressed in the form of a ghost in these movies. The research found that these women cannot express their anger in the real world, which is controlled by the patriarchal order. Life after death is the only space where they can express their anger. Both movies can consequently be interpreted as cultural texts that internalize patriarchal ideology in Japanese and Indonesian society.